2003
DOI: 10.1098/rstb.2003.1346
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cartilage mechanobiology

Abstract: The growth, maintenance and ossification of cartilage are fundamental to skeletal development and are regulated throughout life by the mechanical cues that are imposed by physical activities. Finite element computer analyses have been used to study the role of local tissue mechanics on endochondral ossification patterns, skeletal morphology and articular cartilage thickness distributions. Using single-phase continuum material representations of cartilage, the results have indicated that local intermittent hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 45 publications
2
124
1
Order By: Relevance
“…12,[20][21][22] Specifically, Carter and Wong, 12,23 using a two-dimensional (2D) finite element model, showed that cyclic shear stresses promote endochondral ossification, whereas cyclic compressive dilatational stresses inhibit ossification. These finite element models illustrate that in the developing chondroepiphysis, the region of highest osteogenic index corresponds to the location of the secondary ossification center.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[20][21][22] Specifically, Carter and Wong, 12,23 using a two-dimensional (2D) finite element model, showed that cyclic shear stresses promote endochondral ossification, whereas cyclic compressive dilatational stresses inhibit ossification. These finite element models illustrate that in the developing chondroepiphysis, the region of highest osteogenic index corresponds to the location of the secondary ossification center.…”
Section: Introductionmentioning
confidence: 99%
“…These finite element models illustrate that in the developing chondroepiphysis, the region of highest osteogenic index corresponds to the location of the secondary ossification center. 21,22,[24][25][26] Experimental data obtained by applying intermittent and continuous compressive forces to the 16-day-old metatarsal rudiment of mouse embryo in organ culture demonstrated that the mineral apposition in the primary ossification site in the center of the metatarsal cartilage rudiment is accelerated, with intermittent forces twice as effective as continuous forces. 27 This study suggests that mechanical stresses accelerate the formation of the primary ossification site during prenatal development.…”
Section: Introductionmentioning
confidence: 99%
“…Using the material representation of the continuum phase of cartilage, results have indicated that local intermittent hydrostatic pressure promotes cartilage maintenance (Carter & Wong, 2003).…”
Section: Computational Analysis Of Articular Cartilagementioning
confidence: 99%
“…The reduction of poroelastic behaviour in degenerated discs implies a reduction in hydrostatic pressure. The reduction in hydrostatic pressure will increase the shear stresses in the IVD (Carter and Wong, 2003;Hwang et al, 2012), which is known to have a mechanobiological effect on the IVD cells. The cells respond to shear stress by activation of remodelling genes, which leads to increased production of collagen type-I (Carter and Wong, 2003, Paul et al, 2013).…”
mentioning
confidence: 99%